Association of microRNA expression with changes in immune markers in workers with cadmium exposure. (July 2021) - Goyal, Taru; Mitra, Prasenjit; Singh, Preeti; Ghosh, Raghumoy; Sharma, Shailja; Sharma, Praveen
Abstract: Human exposure to cadmium (Cd) is known to produce severe health effects. Recently, molecular mechanism of Cd toxicity has revealed the role of Cd in causing epigenetic alterations. miRNAs are small, non-coding RNAs which are involved in translational repression of genes. Therefore, the aim of the present study was to evaluate the alterations in expression of miRNAs associated with inflammation, carcinogenesis and, further, study their possible correlation with immune profile, in occupationally Cd exposed workers of Jodhpur. 106 workers from metal handicraft and welding factories were recruited as subjects, while, 80 apparently healthy non-exposed individuals served as control for this study. Blood Cd levels (BCd) were determined by Graphite Furnace Atomic Absorption Spectroscopy (GFAAS). Lymphocyte cell subset were measured by flow cytometry, serum interleukins were assessed by ELISA and miRNA expression was determined by Real Time Polymerase Chain Reaction (RT-PCR). BCd levels were significantly higher in the exposed individuals when compared to the non-exposed, with welders reporting the highest amongst all. Among the lymphocyte subset, exposed group showed significantly higher percentage of Th17 and lower percentage of Treg population. Cytokine profile expressed by exposed workers were predominantly pro-inflammatory in nature. Among, the studied miRNAs, miR-221 was significantly higher in exposed group with a fold change of 3.05. Additionally, miR-221 and miR-155 showed significant positive correlation with Th17 cell %. Regression analysis showed duration of exposure and IL-17 to have significant effect on miR-221 in exposed group. In conclusion, miR-221 was significantly upregulated in exposed and was correlated with immune alteration making it a potential candidate for further exploration of mechanism underlying Cd toxicity. Highlights: Higher blood cadmium levels are associated with alteration in immune markers with a predominant pro-inflammatory state. Cadmium exposure may result in epigenetic changes in workers occupationally exposed to this metal. Increased Cd levels may result in upregulation of miR-221which is associated with alteration in immune response.